8200‐year growth history of a Lahontan‐age lacustrine tufa deposit. Issue 6 (14th March 2019) - Demott, Laura M.; Scholz, Christopher A.; Junium, Christopher K.
Abstract: Tufa domes and towers are common around the margins of Winnemucca Dry Lake, Nevada, USA, a desiccated sub‐basin of pluvial Lake Lahontan. A 2·5 m diameter concentrically‐layered tufa mound from the southern end of the playa was sampled along its growth axis to determine timing, rate and geochemical conditions of tufa growth. A radiocarbon‐based age model indicates an 8200‐year tufa depositional record that begins near the end of the Last Glacial Maximum ( ca 23 400 cal yr bp ) and concludes at the end of the most recent Lahontan highstand ( ca 15 200 cal yr bp ). Petrography, stable isotopes and major and minor elemental compositions are used to evaluate the rate and timing of tufa growth in the context of the depositional environment. The deposit built radially outward from a central nucleation point, with six decimetre‐scale layers defined by variations in texture. Two distinct tufa types are observed: the inner section is composed of two layers of thinolite pseudomorphs after ikaite, with the innermost layer comprised of very small pseudomorphs (<0·25 cm) and an outer layer composed of larger, ca 3 cm long pseudomorphs, followed by a transitional layer where thinolite pseudomorphs grade into calcite fans. The outer section consists of three distinct layers of thrombolitic micrite with a branching mesofabric. The textural change occurred as lake levels began to rise towards the most recent Lahontan highstand interval and probably was prompted by warming of lake waters caused by increased groundwater flux during highstand lake levels. The Mg/Ca and Sr/Ca variations suggest a warming trend in the tufa growth environment and may also reflect increasing growth rates of tufa associated with increased fluxes of groundwater. This systematic study of tufa deposition indicates the importance of the hydrology of the lacustrine tufa system for reconstructing palaeoenvironmental records, and particularly the interaction of ground and surface waters.